The Nathan narratives - Jones, Gwilym H. (Gwilym Henry), 1930- (Journal for the study of the Old Testament. Supplement series ;, 1990)
The three Nathan narratives in 2 Samuel and 1 Kings, are given detailed consideration in this fascinating study. A persuasive attempt is made to reconstruct the original form of the traditions and to trace the modifications made to them before they were finally accepted into the Succession Narrative. The original Nathan, a court official and chief spokesman for the Jebusite group, sought a working compromise between the original Jebusite inhabitants of Jerusalem and its new Israelite settlers. After accepting service under King David, Nathan tried to secure the best he could for the Jebusites.